Implementation of the Picture and Picture Learning Model for Grade IV Students at SDIK Asy-Syafi'i - Imas Masripah; Jihan Magrfirah (Teunuleh Publisher, 2026)
This study aimed to determine the effectiveness of the application of the Picture and Picture learning model in improving the learning outcomes of students in the subject of Islamic Religious Education in grade IV of SDIK Asy-Syafi'i. This study used a quantitative approach with a pre-experimental design method in the form of a one-group pretest-posttest design. The participants were 18 students. Data were collected through learning outcome tests in the form of pre- and post-tests. The data obtained were then analyzed using the calculation of the average and Normalized Gain (N-Gain). The results showed that the average pre-test score of 66.39 increased to 85.00 in the post-test, with an increase of 19.11 points. The N-Gain value obtained was 0.66, which was in the medium category. In addition, the completeness of students' learning increased from 44% to 78%. These results demonstrate that the application of the PiPeL model is effective in improving student learning outcomes. This model can increase students' activity and understanding through the use of visual media in the learning process. Thus, the PiP learning model can be used as an alternative to improve the quality of learning, especially in the subject of Islamic Religious Education in elementary schools.